The golden target: analyzing the tracking performance of leveraged gold ETFs. Issue 3 (3rd August 2015) - Leung, Tim
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to understand the tracking errors of leveraged exchange-traded funds (LETFs) on gold and demonstrate improved tracking performance by dynamic portfolios of gold futures. Design/methodology/approach – The author formulates and solves a constrained quadratic minimization problem to construct static replicating portfolios of both leveraged and unleveraged benchmarks in gold; a dynamic constant leveraged portfolio using gold futures is used to track the path of the leveraged gold benchmark. Findings – The results suggest that market-traded LETFs do not track a leveraged position in gold effectively over a long horizon, and the dynamic leveraged futures portfolio achieves lower tracking errors over multiple years. Research limitations/implications – The research informs us that investors should consider alternative portfolios with gold futures, rather than holding a leveraged gold exchange-traded funds to achieve a desired leveraged exposure in spot gold. Originality/value – The main contribution of the study is the use of gold futures to dynamically replicate a gold benchmark with any given leverage ratio and the detailed comparison of the tracking performance of LETFs versus optimal static and dynamic futures portfolios.